Deteksi Dini Tanda Bahaya Dengan Pemeriksaan HIV/AIDS - Ice Rakizah Syafrie; Diyah Tepi; Maysah Resti Pratiwi; Kanida Dwi Pastike; Noftriana Angelina (Gayaku Publisher, 2022)
Risk factors for HIV/AIDS include infection/virus, sex, age, history of sexually transmitted infections, education, history of alcohol consumption, history of piercings, family history of HIV/AIDS, knowledge, more than one sexual partner, environmental factors, risky sexual behavior, and unprotected sex. Another impact caused by HIV/AIDS is not only a health problem, but the psychosocial impact also has a significant contribution to women's welfare. Women affected by HIV/AIDS psychologically will experience various problems, ranging from lack of confidence, hopelessness, anxiety, doubt, stress, and depression to discrimination. The community service team from the Unived FIKes Midwifery Study Program (DIII), in collaboration with the Pesona Institute of Bengkulu Province, held early detection of danger signs with HIV/AIDS examinations, which aimed to prevent the occurrence of HIV/AIDS from an early age, especially in the productive period (adolescents and couples of childbearing age), as an effort in order to prepare for premarital, preconception, and reproductive processes that are healthy and of good quality. The method used in this service is by providing KIE (communication, information, and education) and screening in the form of an HIV/AIDS examination. By providing health education, it is hoped that the incidence of HIV/AIDS can be minimized or prevented.